Electrical safety in a hospital setting: A narrative review - Loganathan Salvaraji; Mohammad Saffree Jeffree; Khamisah Awang Lukman; Sahipudin Saupin; Richard Avoi (Elsevier Ltd, 2022)
Electrical hazard is a significant threat in hospitals that require sustainable assessment and improvement. Workplace assessment and medical surveillance systems are often overlooked, and employees fail to comply with the necessary measures that have been instructed at the workplace. The incidents are attributed to a lack of knowledge regarding occupational safety and health and a lack of awareness regarding electrical hazards importance. The consequences of neglecting these assessments may result in health deterioration and low work quality and may also cause disability and impairment. This review describes occupational safety and health perspective about electrical hazards in hospital settings. Further preventive measures were recommended to outline practical and feasible steps resulting in a safer and healthier working environment.